2022
DOI: 10.1101/2022.10.17.22281085
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 among adults living with HIV: Correlates of mortality in a general population in a resource-limited setting

Abstract: Introduction: While a large proportion of people with HIV (PWH) have experienced SARS-CoV-2 infections, there is uncertainty about the role of HIV disease severity on COVID-19 outcomes, especially in lower income settings. We studied the association between mortality and characteristics of HIV severity and management, and vaccination, among adult PWH. Methods: We analysed observational cohort data on all PWH aged ≥15 years experiencing a diagnosed SARS-CoV-2 infection (until March 2022), who accessed public se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Another cohort study from South Africa also found that CD4 cell count less than 200 cells/μl was independently associated with increased risk of COVID-19 mortality [10 ▪ ]. A third recent South African cohort study found that among PWH, COVID-19 mortality was associated with lower recent CD4 count, high HIV RNA, and no evidence of recent antiretroviral prescription [19 ▪▪ ].…”
Section: Severity Of Coronavirus Disease 2019 In People With Hiv With...mentioning
confidence: 95%
“…Another cohort study from South Africa also found that CD4 cell count less than 200 cells/μl was independently associated with increased risk of COVID-19 mortality [10 ▪ ]. A third recent South African cohort study found that among PWH, COVID-19 mortality was associated with lower recent CD4 count, high HIV RNA, and no evidence of recent antiretroviral prescription [19 ▪▪ ].…”
Section: Severity Of Coronavirus Disease 2019 In People With Hiv With...mentioning
confidence: 95%